ANALYSIS OF STATIC BEHAVIOR OF ION SENSITIVE FIELD EFFECT TRANSISTOR FOR PH MEASUREMENTS - Kevkić, Tijana; Maity, Reshmi; Todorović, Dragana; Vučković, Biljana; Maity, N. P. (Bulletin of Natural Sciences Research, 2022)
The Ion-Sensitive Field-Effect Transistor (ISFET) is one of the most popular pH sensors traditionally using to measure hydrogen ion concentration (pH) of the electrolytic solutions. It is developed from Metal Oxide Semiconductor Field-Effect Transistor (MOSFET) by replacing gate electrode with an electrolytic solution to be tested, and a reference metal electrode immersed in that solution. Basic principle of ISFET operation is based on that of standard NMOS structure in conjunction with the insulator-electrolyte capacitor as described in this paper. The site-binding theory (generalized to two kinds of binding sites), together with the Gouy - Chapman- Stern model for the potential profile in the electrolyte, is coupled to the MOS physics. As a result, an approximate analytical model which completely describes static behavior of the ISFET is obtained. The developed description can serve as useful tool for understanding many contemporary biosensors based on original ISFET structure which has broad application in biomedicine, biological, chemistry and environmental areas.